MITOLOGI SAEDAH SAENIH: CERITA RAKYAT DARI INDRAMAYU - Yuzar Purnama (Patanjala: Journal of Historical and Cultural Research, 2016)
Indramayu community still believe with the customs of his ancestors. In some areas, we can found the traditional arts, beliefs, ceremonies, games and story. On this occasion, the writers wanted to examine folklore mythology Saedah Saenih. The existences of Saenih Saedah story is very attached to some people in Indramayu, as if the story is real.  The story is famous, and it appeared in the drama, lyrics, and even once made into a movie. The problems outlined in the form of questions, the myth of what is contained in the story Saedah Saenih? How far the myth Saedah Saenih for the community? what moral values that is contain in the story Saedah Saenih? This study aims are to get a complete and clear picture of the mythology in Saedah Saenih folklore. This study used a qualitative approach with descriptive method. The study begins literature, data collection, classification, analysis and reporting. In conclusion, the mythical story Saenih Saedah very attached to the people of Indramayu. The contents are considered real story is characterized by the belief that the existence Saenih still in the river Sewo in white crocodile manifestation. Compliance form of throw money, as it passes through the bridge Sewo to avoid disaster. They also believe Sarkawi transformed into a floating bale, Maemunah be pring ori, and Saedah into a tree on the river bank Sewo.